إعادة التوازن المالي في عقد البوت - إشراف بعادشية (My University, 2022)
Summary: The BOT contract is one of the general and effective means of achieving a balance between the objectives of both the public and private sectors, and the establishment of new infrastructure-related facilities. Although the Algerian legislator did not know the BOT contract, he took it within the framework of the concession contract, with the aim of establishing and running the BOT contract. Public utilities using modern methods, and the most important thing raised in this regard is the idea of rebalancing the financial system for it, as a right granted to the contractor with the administration. ......................... :ملخص المذكرة يعد عقد البوت من الوسائل العامة والفعالة في تحقيق التوازن بين أهداف كل من القطاعين العام والخاص، وإقامة المنشآت الجديدة الخاصة بالبنى التحتية. BOT إلا أنه أخذ به في إطار عقد وبالرغم من أن المشرع الجزائري لم يعرف عقد البوت الامتياز، وذلك بهدف إنشاء وتسيير المرافق العامة بأساليب حديثة، وأهم ما يثار بصدده فكرة إعادة التوازن المالي له، كحق مخول للمتعاقد مع الإدارة.